(untitled) (EAAE Annual Conference Proceedings, 2025)
The increasing requirements regarding the level of education of architecture students and their competences necessary for their future work are a constant challenge for academic teachers. Curricula are constantly being transformed to reconcile the tradition of architectural schools with the complexities of the present. This paper discusses examples of new topics for freehand drawing courses, taught to students of Landscape Architecture at the Faculty of Architecture Cracow University of Technology (CUT) in Poland. They used real projects and teamwork (Project Based Learning, Problem Based Learning). An example of such activities is participa- tion in: (1) the plein air drawing and painting in Hrubieszów carried out as part of the research project “Local develop- ment of Hrubieszów: from participation to implementation” financed by the “Local Development Programme” under the Financial Mechanism of the European Economic Area; (2) the competition on the occasion of 80th CUT anniversary; (3) the poster competition that engages students in the search for innovative visions of the entrance to the Krakow metro. The article is based on the latest scientific research on implementing Project Based Learning and Problem Based Learning in architectural education. It also uses the observational method based on many years of pedagogical experience and the experimental method. The aim of the article is to show that the implementation of authentic projects (close to real challenges in the future profession) and topics based on cooperation during freehand drawing classes contribute to greater engagement (seeing the specific purpose of the work and its meaning, students are more motivated), development of soft skills (communication, teamwork, negotiation), better assimilation, and long-term memory of experiences. It prepares them better for the future work of an architect, in which problem-solving and creative thinking are very important. The article concludes that drawing skill becomes an antidote to the dehumanising effects of artificial intelligence and mechanised learning. The engaging process of drawing becomes a pretext to meet one’s own thoughts and confront peers. Involving students in solving real problems, during the pleasant drawing process, teaches them independence, cooperation, and communication. This method is more effective and increases learning outcomes.